Suppression of Breast Cancer Cell Migration and Epithelial-Mesenchymal Transition by Atmospheric Pressure Plasma - Kim, Kijung; Choung, Jinseung; Ko, Ung Hyun; Jung, Ara; Choe, Wonho; Shin, Jennifer H.; Gweon, Bomi (Frontiers in Physics, 2021)
Atmospheric pressure plasma (APP) has emerged rapidly as a potent tool for cancer therapy thanks to its multiple anti-cancer effects. Depending on the types, APP has been shown to induce necrosis, apoptosis, or senescence in cancer cells in vitro and reduce tumor size in vivo. While recent progress in plasma medicine has led to various hypotheses for the molecular mechanism of APP, the key effector in anti-cancer processes still remains elusive. In this study, we show that APP treatment on an invasive breast cancer cell line (MDA-MB-231) dramatically alters these cells' morphology and further suppresses migratory activity. In addition to the functional changes, epithelial to mesenchymal transition (EMT) markers, such as vimentin and alpha-smooth muscle actin (α-SMA), were found to be down-regulated in MDA-MB-231 by the APP treatment. As a result, APP treatment appears to impact the invasive nature of cancer cells, motivating the possible use of APP as a therapeutic tool to suppress cancer metastasis.